(untitled) (Medical Forum Monthly, 2022)
Objective: To analyze demographic profiles, frequency, morbidity and mortality of Aluminium Phosphide (wheat pill) poisoning cases reported at accident and emergency department of Bahawal Victoria Hospital Bahawalpur between the years 2019 to 2021. Study Design: Retrospective Study Place and Duration of Study: This study was conducted at the A&E Department B.V Hospital Bahawalpur, over a period of three years from 1st January 2019 to 31st December 2021. Materials and Methods: Data of a total of 104 cases was analysed with regard to age and gender distribution, morbidity and mortality. Results: Out of 104 cases, most common age group was 20-40 years and commonly, the female predominance of 72% is noted among all cases. The mortality rate calculated as 54.8%. Conclusion: Aluminium Phosphide is a readily available lethal poison and with no specific antidote. Aluminium Phosphide poisoning is associated with high mortality and suicide predominantly among females and in younger age groups.. Multiple approaches are required to reduce mortality and morbidity associated with intentional poisoning.